2018
DOI: 10.3389/fict.2018.00021
|View full text |Cite
|
Sign up to set email alerts
|

Digital Inclusion in Older Adults: A Comparison Between Face-to-Face and Blended Digital Literacy Workshops

Abstract: As information and services are becoming more and more decentralized and they are often available in the cloud, an increasing number of older adults are expected to use Internet-based services-health, education, finance and others. For this reason, it seems important to plan models and/or strategies to allow the older adult population to acquire and enhance digital competencies more easily. The goal of this research is to show a blended workshop based on a Learning Management System (LMS) as a supporting tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 32 publications
1
94
0
1
Order By: Relevance
“…Digital literacy is a set of skills associated with the use of ICT that every individual should develop to be able to perform in a computerized society [ 59 ]. Many informal caregivers are middle-aged to older people with a low to middle educational level [ 16 ], and these sociodemographic characteristics are often associated with a low level of digital skills, which could prevent them from benefiting from ICT [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital literacy is a set of skills associated with the use of ICT that every individual should develop to be able to perform in a computerized society [ 59 ]. Many informal caregivers are middle-aged to older people with a low to middle educational level [ 16 ], and these sociodemographic characteristics are often associated with a low level of digital skills, which could prevent them from benefiting from ICT [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lamura et al [ 12 ] highlighted the importance of improving older informal caregiver digital literacy based on an early assessment of their needs and digital skills. Research showed that older adults are capable of learning and acquiring digital literacy skills as long as they know the functional benefits related to ICT [ 59 ]. Thus, this is in line with another recommendation in this theme to combine the utility of the internet with the expertise of medical professionals, including care-support hotlines, to improve informal caregiver trust in technology solutions and their functional benefits.…”
Section: Discussionmentioning
confidence: 99%
“…An Agewell Foundation Study found about 85.8% of older adults in India were digitally illiterate ( Agewell, 2020 ). Contrary to the myth of older people being unable to master new skills, studies using blended pedagogy-based learning modules have demonstrated that older adults are capable of acquiring digital literacy ( Martinez-Alcala et al., 2018 ). However, little to no efforts have been made to engage older adults in digitization during the pandemic.…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…Previous studies have investigated ATM use experience in old age [14], relating the evaluation of technophobia to agreement regarding general statements on technology; and the internet effect on digital inclusion outcomes regarding users and their views of business and internet/online skills [15,16,17,18]. A further interesting topic is the impact of technology in the cognitive development [19,20,21,22,23,24] and improvement of cognitive ability in older adults [25,26,27,28,29]. An emerging topic that, so far, has been lacking research is the impact of technology on human living with respect to digital solutions adapted to the needs of individuals and society.…”
Section: Introductionmentioning
confidence: 99%